2021
DOI: 10.1016/j.jaut.2021.102741
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis after COVID-19 vaccine – more than a coincidence

Abstract: The COVID-19 pandemic is still raging across the world and vaccination is expected to lead us out of this pandemic. Although the efficacy of the vaccines is beyond doubt, safety still remains a concern. We report a case of a 65-year-old woman who experienced acute severe autoimmune hepatitis two weeks after receiving the first dose of Moderna-COVID-19 vaccine. Serum immunoglobulin G was elevated and antinuclear antibody was positive (1:100, speckled pattern). Liver histology showed a marked expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 4 publications
1
71
1
2
Order By: Relevance
“…Findings in liver biopsy correlate with reports of AIH following SARS-CoV-2 vaccination. Necroinflammatory hepatitis was observed in all cases of AIH following vaccination with Moderna mRNA-1273 COVID-19 [ [24] , [25] , [26] , [27] , [28] , [29] ], Pfizer-BioNTech mRNA vaccine [ [30] , [31] , [32] , [33] ], and AstraZeneca ChAdOx1 nCoV-19 vaccine [ 8 , 34 ]. It has been suggested that portal infiltration with eosinophils correlates with drug-induced liver injury, including vaccines (i.e., Moderna mRNA-1273 and AstraZeneca ChAdOx1 nCoV-19 vaccines) [ 8 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings in liver biopsy correlate with reports of AIH following SARS-CoV-2 vaccination. Necroinflammatory hepatitis was observed in all cases of AIH following vaccination with Moderna mRNA-1273 COVID-19 [ [24] , [25] , [26] , [27] , [28] , [29] ], Pfizer-BioNTech mRNA vaccine [ [30] , [31] , [32] , [33] ], and AstraZeneca ChAdOx1 nCoV-19 vaccine [ 8 , 34 ]. It has been suggested that portal infiltration with eosinophils correlates with drug-induced liver injury, including vaccines (i.e., Moderna mRNA-1273 and AstraZeneca ChAdOx1 nCoV-19 vaccines) [ 8 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that portal infiltration with eosinophils correlates with drug-induced liver injury, including vaccines (i.e., Moderna mRNA-1273 and AstraZeneca ChAdOx1 nCoV-19 vaccines) [ 8 , 27 , 28 ]. This could partially explain the existence of hepatitis following vaccination without positivity for liver-associated autoantibodies ( Table 1 ) [ 8 , 10 , 12 , 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous cases, this patient had received the Oxford-AstraZeneca vaccine, an adenovirus-based vaccine. Chow et al [ 18 ] recently conducted a systematic search of the literature about the documented cases of AIH following COVID-19 vaccination [ 14–17 , 19–30 ]. They reported that 29 patients received mRNA vaccines and three patients received the Oxford-AstraZeneca vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The AEs post-vaccination usually were mild, self-limited and non-fatal including the local AEs such as pain at injection site and systemic events such as fever, fatigue, flu-like symptoms and myalgia (75)(76)(77)(78). There have been case report and case series of acute liver injury after mRNA vaccination (114)(115)(116)(117). Shroff et al (114) reported 10 of 16 patients required hospitalization and therapy with good recovery.…”
Section: Safety Of Covid-19 Vaccine For Cld and Lt Recipientsmentioning
confidence: 99%